2019
DOI: 10.4244/eij-d-18-00779
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and durability of the CoreValve transcatheter aortic bioprosthesis: outcomes beyond five years

Abstract: Aims: to determine long-term outcomes of high-risk patients who underwent transcatheter aortic valve implantation (TAVI) with third-generation CoreValve device, according to the 2017 EAPCI/ESC/EACTS definition of valve durability.Methods and results: between 2007 and 2013, 278 consecutive patients were enrolled in our prospective single-centre CoreValve registry (mean age 82±6 years, mean STS score 6.4±5.0%); median follow-up of survivors was 6.8 years. The Cox proportional hazards model was used to identify i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The Notion trial has a follow-up of up to 6 years assessing valve durability comparing TAVR and SAVR [32]. These studies demonstrated no alarm concerning transcatheter durability [33], 3.3% of patients had undergone valve implantation again due to paravalvular leakage [34] and a majority of patients showed mild/ trivial paravalvular leakage during long-term follow-up [35]. Results on valve performance with a follow-up of 5 years are promising, however, the number of studies is limited and assessment in younger and lower-risk patients is required [33].…”
Section: Expert Opinionmentioning
confidence: 99%
“…The Notion trial has a follow-up of up to 6 years assessing valve durability comparing TAVR and SAVR [32]. These studies demonstrated no alarm concerning transcatheter durability [33], 3.3% of patients had undergone valve implantation again due to paravalvular leakage [34] and a majority of patients showed mild/ trivial paravalvular leakage during long-term follow-up [35]. Results on valve performance with a follow-up of 5 years are promising, however, the number of studies is limited and assessment in younger and lower-risk patients is required [33].…”
Section: Expert Opinionmentioning
confidence: 99%
“…ranscatheter aortic valve implantation (TAVI) has emerged as an alternative treatment for patients with aortic stenosis (AS) who are at intermediate to high risk for surgery, 1,2) and the procedure exhibited a convincing long-term efficacy. With the emergence of new TAVI systems, transcatheter heart valve (THV) devices with different support frame designs were used in interventional treatment for aortic disease.…”
mentioning
confidence: 99%
“…After the introduction of EAPCI/ESC/EACTS standardised criteria of SVD in 2017, an increasing number of studies have been reporting outcomes after TAVI with either the SAPIEN (Edwards Lifesciences) or CoreValve TAVs up to 7 and 8 years ( Table 4 ). [3841] Three single-centre studies demonstrated stable trans-prosthetic gradients over time and a rate of severe TAV dysfunction of 2.4%, 3.2% and 3.6%. [3941] Holy et al analysed long-term outcomes of 152 consecutive patients who had undergone TAVI with the self-expanding CoreValve between 2007 and 2011.…”
Section: Bioprostheses Durability Datamentioning
confidence: 99%
“…[3841] Three single-centre studies demonstrated stable trans-prosthetic gradients over time and a rate of severe TAV dysfunction of 2.4%, 3.2% and 3.6%. [3941] Holy et al analysed long-term outcomes of 152 consecutive patients who had undergone TAVI with the self-expanding CoreValve between 2007 and 2011. [42] Echocardiographic follow-up was achieved at 6.3 ± 1.0 years (5.0–8.9 years) and was 88% complete (60 of the 68 participants who survived beyond 5 years).…”
Section: Bioprostheses Durability Datamentioning
confidence: 99%